Percolation-amplified infrared sensitivity in titanium oxide-multi-walled carbon nanotube composite films. (21st March 2019) - Liang, Qian; Xu, Xiangdong; Zhou, Huaxin; Park, Junsung; Xu, Jimmy; Jiang, Yadong; Cheng, Xiaomeng; Gu, Yu
Abstract: Titanium dioxide (TiO2 )-multi-walled carbon nanotube (MWCNT) thin films were prepared and studied systematically for the effects of the concentration of MWCNTs on the electro-optical properties. Result shows that the addition of MWCNTs not only improves the optical absorption and electrical conductivity, but also reduces the 1/ f noise of the films. Percolation phenomenon is observed at MWCNT concentrations of 0.20–0.25 wt%. In this concentration range, the composite films exhibit an abrupt rise of the temperature coefficient of resistance value (−2.93% K −1 ) and large general thermal parameter, both of which are desirable for applications in uncooled infrared detectors.